2021
DOI: 10.3390/cancers13205116
|View full text |Cite
|
Sign up to set email alerts
|

Which Tyrosine Kinase Inhibitors Should Be Selected as the First-Line Treatment for Chronic Myelogenous Leukemia in Chronic Phase?

Abstract: With the use of tyrosine kinase inhibitors (TKIs), chronic myelogenous leukemia in chronic phase (CML-CP) has been transformed into a non-fatal chronic disease. Hence, "treatment-free remission (TFR)" has become a possible treatment goal of patients with CML-CP. Currently, four types of TKIs (imatinib, nilotinib, dasatinib, and bosutinib) are used as the first-line treatment for newly diagnosed CML-CP. However, the second-generation TKI (2GTKI), the treatment response of which is faster and deeper than that of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…These treatment modalities are suitable for chronic CML. Several studies have shown that switching from imatinib to 2G–TKI shortened the time between DMR and TFR, so some studies have suggested the use of 2GTKI as a first–line treatment option for female patients with CML–CP who desire pregnancy ( 28 ). This view needs further validation because of the increased cost of 2G–TKI, the severe side effects, and the lack of extensive clinical data.…”
Section: Discussionmentioning
confidence: 99%
“…These treatment modalities are suitable for chronic CML. Several studies have shown that switching from imatinib to 2G–TKI shortened the time between DMR and TFR, so some studies have suggested the use of 2GTKI as a first–line treatment option for female patients with CML–CP who desire pregnancy ( 28 ). This view needs further validation because of the increased cost of 2G–TKI, the severe side effects, and the lack of extensive clinical data.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying appropriate patient candidates, timing of treatment initiation or dose adjustment, and consideration of numerous patient factors, including disease risk, molecular factors, efficacy and tolerability of prior treatments, patient age, comorbidities, and individual patient goals, are all crucial. 93 …”
Section: Considerations For Patient Selection For Asciminibmentioning
confidence: 99%
“…Specifically, they are associated with cardiovascular, pulmonary, pancreatic, and hepatic toxicities [3]. In the ENESETnd study, 10-year cumulative incidence of cardiovascular events was 24.8% in the nilotinib (300 mg bid) arm as opposed to 6.3% in the imatinib arm [7]. Nilotinib is also associated with glucose tolerance and dyslipidemia, and its use in patients with cardiovascular risk factors or diabetes requires careful consideration.…”
Section: Second-generation-tkis Have No Survival Benefit But Have Gre...mentioning
confidence: 99%